Cultural Dimension of Security Sector Ethics - Bulatović, Aleksandra; Korać, Srđan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
The article focuses on ethics as a social and cultural factor impacting the work of the security services, with a special view of the role the security sector-specific culture plays vis-à-vis the democratic quality of security. Ethics is a key factor that shapes professionals' attitudes and affects the way they perform. While operating in accordance with its instrumental social function (addressing security threats), institutions of the security sector must at the same time act as keepers of the social values. The appraisal of security measures and practices is subject to the ultimate requirement to uphold social order and a quality of life within the framework of social values, and not just to be instrumentally effective. The paper considers the nature of the security service's ethics and the relationship between the culture of a security service and the way it affects the state’s overall exercise of power over the citizens.